2015
DOI: 10.1016/j.bbrc.2015.01.132
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state and time-resolved Thioflavin-T fluorescence can report on morphological differences in amyloid fibrils formed by Aβ(1-40) and Aβ(1-42)

Abstract: Thioflavin-T (ThT) is one of the most commonly used dyes for amyloid detection, but the origin of its fluorescence enhancement is not fully understood. Herein we have characterised the ThT fluorescence response upon binding to the Aβ(1-40) and Aβ(1-42) variants of the Alzheimer's-related peptide amyloid-β, in order to explore how the photophysical properties of this dye relates to structural and morphological properties of two amyloid fibril types formed by peptides with a high degree of sequence homology. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 34 publications
9
56
1
Order By: Relevance
“…ThT is a fluorescent dye which preferentially binds to β -sheet-rich amyloid aggregates, yielding an increase in fluorescence intensity. 42,43 A 3-fold molar excess (75 µ M) of polymer was incubated with A β (25 µ M) in 20 mM Tris at pH 8.0 with 0.1 M NaNO 3 and 0.01% NaN 3 . Samples were kept at 37 °C, and ThT fluorescence was measured periodically (Figure 3A–C).…”
Section: Resultsmentioning
confidence: 99%
“…ThT is a fluorescent dye which preferentially binds to β -sheet-rich amyloid aggregates, yielding an increase in fluorescence intensity. 42,43 A 3-fold molar excess (75 µ M) of polymer was incubated with A β (25 µ M) in 20 mM Tris at pH 8.0 with 0.1 M NaNO 3 and 0.01% NaN 3 . Samples were kept at 37 °C, and ThT fluorescence was measured periodically (Figure 3A–C).…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that the amyloid formation reactions with FL proteins do not have the same amount of amyloid formed at the end of the reactions. The other explanation is that the structure of the amyloid formed by FL proteins does not allow as many ThT binding sites as the structure for V L amyloid or that the affinity of each binding site is different [19]. In addition, it is possible that ThT molecules bound to the different fibrils have different fluorescence quantum yields.…”
Section: Resultsmentioning
confidence: 99%
“…In situations where there is effectively only one aggregated species (such as the end of the reaction) the weight normalized ThT value is characteristic of the polymorphic state of the aggregate. Previously we showed that structurally different polymorphic forms of mature Aβ 40 fibrils exhibit different weight-normalized ThT intensities 39 , and it was recently suggested that such intensity variations are due to differences in the number of ThT binding sites (normally considered to be in β-sheet 40 ) in an aggregate 41 .…”
Section: Resultsmentioning
confidence: 99%